2021
DOI: 10.1021/acsphotonics.1c00601
|View full text |Cite
|
Sign up to set email alerts
|

Antireflective Huygens’ Metasurface with Correlated Disorder Made from High-Index Disks Implemented into Silicon Heterojunction Solar Cells

Abstract: A large variety of different strategies has been proposed as alternatives to random textures to improve light coupling into solar cells. While the understanding of dedicated nanophotonic systems deepens continuously, only a few of the proposed designs are industrially accepted due to a lack of scalability. In this Article, a tailored disordered arrangement of high-index dielectric submicron-sized titanium dioxide (TiO2) disks is experimentally exploited as an antireflective Huygens’ metasurface for standard he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 54 publications
(100 reference statements)
0
19
0
Order By: Relevance
“…By contrast, HUD point patterns naturally arise in many physical systems, which can lead to simple and scalable fabrication of the HUD holes or HUD network patterns. For instance, it has been shown that the structure factor of dispersed colloidal particle (e.g., beads) patterns can be tuned by the ionic strength of the particular solvent and that the dewetting or phase separation of dielectric layers leads to HUD patterns. , Also, soft-imprint conformal lithography has proven an excellent low-cost alternative to pattern large-areas with a resolution below 10 nm that could actually serve for both HUD holes and HUD network . While a master substrate has to be first made with other lithography methods (such as e-beam lithography), the master can be extensively reused for the creation of multiple-use soft stamps.…”
Section: Resultsmentioning
confidence: 99%
“…By contrast, HUD point patterns naturally arise in many physical systems, which can lead to simple and scalable fabrication of the HUD holes or HUD network patterns. For instance, it has been shown that the structure factor of dispersed colloidal particle (e.g., beads) patterns can be tuned by the ionic strength of the particular solvent and that the dewetting or phase separation of dielectric layers leads to HUD patterns. , Also, soft-imprint conformal lithography has proven an excellent low-cost alternative to pattern large-areas with a resolution below 10 nm that could actually serve for both HUD holes and HUD network . While a master substrate has to be first made with other lithography methods (such as e-beam lithography), the master can be extensively reused for the creation of multiple-use soft stamps.…”
Section: Resultsmentioning
confidence: 99%
“…[ 9,10 ] However, in the crystalline solid phase, aggregates and crystal faults lead to an increase in density fluctuations. We note that even though the obtained structures in the present study do not qualify as effectively hyperuniform, for some applications, e.g., HuD antireflection structures for solar cells, [ 11 ] even a gradual improvement of hyperuniformity is advantageous. Hence, the patterns obtained in the present study may still be of technological use.…”
Section: Discussionmentioning
confidence: 70%
“…The isotropic nature of DHU structures has enabled the first implementation of isotropic PBGs. [5,6] Moreover, DHU structures have attracted attention in numerous application fields of optics, including light management in solar cells, [7] solid-state lighting, [8] Disordered hyperuniformity (DHU) is one of the most prominent manifestations of the engineered disorder, which aims to circumvent limitations commonly related to order. Considering the k-space, isotropic DHU is characterized by an isotropic suppression of scattering for wavenumbers k approaching zero.…”
Section: Light-controlled Fabrication Of Disordered Hyperuniform Meta...mentioning
confidence: 99%
“…The isotropic nature of DHU structures has enabled the first implementation of isotropic PBGs. [ 5,6 ] Moreover, DHU structures have attracted attention in numerous application fields of optics, including light management in solar cells, [ 7 ] solid‐state lighting, [ 8 ] waveguide polarizers, [ 9 ] surface‐enhanced Raman spectroscopy (SERS), [ 10 ] and tailored light scatterers. [ 11 ]…”
Section: Introductionmentioning
confidence: 99%